Mothers' Union Histories and the Mental and Physical Health of Adolescents Born to Unmarried Mothers. (September 2013) - Williams, Kristi; Sassler, Sharon; Frech, Adrianne; Addo, Fenaba; Cooksey, Elizabeth
As nonmarital childbearing becomes a dominant pathway to family formation, understanding its long-term consequences for children's well-being is increasingly important. Analysis of linked mother-child data from the 1979 National Longitudinal Survey of Youth indicates a negative association of having been born to a never-married mother with adolescent self-assessed health but not with depressive symptoms. We also consider the role of mothers' subsequent union histories in shaping the adolescent health outcomes of youth born to unmarried mothers. With two exceptions, unmarried mothers' subsequent unions appear to have little consequence for the health of their offspring during adolescence. Adolescents whose mothers subsequently married and remained with their biological fathers reported better health, yet adolescents whose mothers continuously cohabited with their biological fathers without subsequent marriage reported worse adolescent mental health compared with adolescents whose mothers remained continually unpartnered.